Rationales for technology-specific RES support and their relevance for German policy. (March 2017) - Gawel, Erik; Lehmann, Paul; Purkus, Alexandra; Söderholm, Patrik; Witte, Katherina
Abstract: In order to achieve cost-effective RES-E deployment it is often argued that technology-neutral support schemes for renewables are indispensable. Against this background, RES-E support policies making widely use of technology differentiation in remuneration settings, e.g. across the EU, are frequently criticized from a theoretical point of view. However, in this paper we provide a systematic critique of the technology neutrality concept as a foundation for designing policy support schemes in the RES-E technology field. Specifically, the main objective of the paper is to scrutinize the arguments for technology-neutrality, and discuss three conceptual arguments for why technology-specific support schemes could in fact help minimize the societal costs of reaching future RES-E targets. We also briefly address different political economy concerns, which could constrain the choice of cost-effective policy support schemes, and that have to be taken into account for economic policy advice. For empirical illustration of the key arguments we refer to the case of German RES-E policy-making. The central conclusion from this paper is that technology-specific RES-E support schemes may generate significant economic benefits, particularly if technology markets work imperfectly and in second-best policy settings with additional non-internalized market failures. Highlights: Three theoretical cost-effectiveness reasons for technology-specific RES-E support. German case study to show relevance of theoretical arguments for policy-making. Political economy constraints to technology-neutral support are demonstrated. Technology-specific RES-E support may generate significant economic benefits.